Influência da fonte de carbono para a recuperação de recursos em sistemas de tratamento de esgoto por granulação aeróbia. - Santos, Amanda Ferreira dos (2022)
The recovery of resources produced in wastewater treatment plants (WWTP) is an economically sustainable alternative for managing excess sludge. In aerobic granular sludge (AGS) systems, extracellular polymeric substances (EPS) content can reach up to 40% of the biomass, giving AGS a great potential to recover exopolymers of great industrial interest. It is known that alginate-like exopolymers (ALE) and tryptophan (Trp) are present in the extracellular matrix of aerobic granules. However, few studies have been carried out to understand the impacts of operational parameters on the biosynthesis of these biopolymers in the sludge. In this context, this study evaluated the influence of different carbon sources on ALE and Trp productions in LGA systems by operating five sequential batch reactors (SBR) with acetate, propionate, glycerol, glucose, and sucrose as substrate sources. In the presence of acetate, an abundance of EPS-producing bacteria was found, as well as the highest biopolymers levels (418.7 mgALE∙gVSS-1 and 4.1 mgTrp∙gVSS-1). However, a partial disintegration of its granules was observed during the operation. On the other hand, during granulation, encouraging results on ALE production (> 250 mgALE∙gVSS-1) were obtained with propionate (R2), significantly higher than those found with glycerol, glucose, and sucrose. However, at the experiment completion, the mature granules fed with propionate no longer produced the same amount of ALE, obtaining values of about 70-90 mgALE∙gVSS-1, close to the results found with glycerol and sucrose. Regarding tryptophan production, in addition to acetate, both propionate and glycerol were shown to be good substrates, with a content of 1.6 mgTrp∙gSSV-1. The granules obtained with glucose showed the worst results compared to the other substrates, 38.5 mgALE∙VSS-1 and 0.6 mgTrp∙gVSS-1, possibly due to the abundance of filamentous microorganisms found in this reactor. Therefore, the carbon source has a high impact on ALE and Trp production.